Strategi Lima Kalimat Dikte: Rumus UPT SDN 19 Parambahan untuk Membedakan huruf Melalui Latihan Harian - Abdul Halim; Aisha Alvania; Alya Rahma (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Difficulty distinguishing letters ‘b’ and ‘d’ is a common obstacle in early writing instruction in elementary schools. This study aims to describe the implementation of a five-sentence daily dictation strategy as a formula for distinguishing these two letters at UPT SD 19 Parambahan, Tanah Datar Regency. A descriptive qualitative approach was employed. Data were collected through direct observation, in-depth interviews with the second-grade teacher, and documentation of learning activities. The results showed that the teacher applied daily dictation of five sentences accompanied by a point system (20 points per perfect line), direct correction, and a differentiated approach for students with special needs. Word wall media, blackboard examples, and the habit of reading before and after writing supported the success of this strategy. The main finding recorded a decrease in error rates in distinguishing letters ‘b’ and ‘d’ from 45% to 7% within four weeks. This study concludes that consistent daily dictation practice is an effective practical formula for overcoming letter discrimination difficulties in second-grade students. This article is expected to serve as a reference for teachers in designing systematic and sustainable writing instruction.